Brain Regional and Temporal Changes in BDNF mRNA and microRNA-206 Expression in Mice Exposed to Repeated Cycles of Chronic Intermittent Ethanol and Forced Swim Stress. (15th May 2019) - Solomon, Matthew G.; Griffin, William C.; Lopez, Marcelo F.; Becker, Howard C.
Abstract: Brain-derived neurotrophic factor (BDNF) expression and signaling activity in brain are influenced by chronic ethanol and stress. We previously demonstrated reduced Bdnf mRNA levels in the medial prefrontal cortex (mPFC) following chronic ethanol treatment and forced swim stress (FSS) enhanced escalated drinking associated with chronic ethanol exposure. The present study examined the effects of chronic ethanol and FSS exposure, alone and in combination, on Bdnf mRNA expression in different brain regions, including mPFC, central amygdala (CeA), and hippocampus (HPC). Additionally, since microRNA-206 has been shown to negatively regulate BDNF expression, the effects of chronic ethanol and FSS on its expression in the target brain regions were examined. Mice received four weekly cycles of chronic intermittent ethanol (CIE) vapor or air exposure and then starting 72-h later, the mice received either a single or 5 daily 10-min FSS sessions (or left undisturbed). Brain tissue samples were collected 4-h following final FSS testing and Bdnf mRNA and miR-206 levels were determined by qPCR assay. Results indicated dynamic brain regional and time-dependent changes in Bdnf mRNA and miR-206 expression. In general, CIE and FSS exposure reduced Bdnf mRNA expression while miR-206 levels were increased in the mPFC, CeA, and HPC. Further, in many instances, these effects were more robust in mice that experienced both CIE and FSS treatments. These results have important implications for the potential link between BDNF signaling in the brain and ethanol consumption related to stress interactions with chronic ethanol experience. Highlights: Chronic ethanol, stress, and their combination alter Bdnf mRNA levels in brain. Chronic ethanol, stress, and their combination alter microRNA-206 levels in brain. Chronic ethanol +/− stress changes in Bdnf mRNA levels are brain region and time-dependent.